Nursing Strategies to Increase Medication Safety in Inpatient Settings. Issue 4 (October 2016) - Bravo, Katherine; Cochran, Gary; Barrett, Ryan
Abstract : Using data obtained through 2 multidisciplinary studies focused on medication safety effectiveness, this article provides nursing recommendations to decrease medication delivery errors. Strategies to minimize and address interruptions/distractions are proposed for the 3 most problematic time frames in which medication errors typically arise: medication acquisition, transportation, and bedside delivery. With planned interventions such as programmed scripts and hospital-based protocols to manage interruptions and distractions, patient safety can be maintained in the inpatient setting.